The Transformation of Urban Tasawuf in Indonesia: Cybermedia and the Emergence of Digital Religion - Rosfiyanti, Nina; Wahidin, Nur; Hannase, Mulawarman (Program Studi Aqidah dan Filsafat Islam, 2024)
This study investigates the influence of cybermedia on urban tasawuf (Islamic mysticism) in Indonesia, focusing on its adaptation to digital platforms and the emergence of a digital religious atmosphere. A qualitative approach grounded in constructivist and interpretivist paradigms was employed. Data were collected through scholarly literature and digital sources, and analyzed thematically to examine key themes, including typologies of urban tasawuf (orthodox, marginal, modern Sufism fellowship) and their interactions with digital media. The findings reveal that urban tasawuf integrates seamlessly with digital technology, enhancing accessibility and fostering spiritual communities. For instance, the tarekat Qudusiyah uses Zoom for dzikr, and the Shift movement integrates youth culture with tasawuf. This adaptation has facilitated the emergence of a uniquely Indonesian expression of digital religion. Urban tasawuf reflects a transformative shift in religious practices through digital adaptation. However, challenges such as one-directional engagement and diluted sacredness pose risks to the depth of spiritual practices. Future research should explore specific phenomena within the paradigm of digital religion, focusing on long-term impacts on religious identity and spirituality.